THEORETICAL FOUNDATIONS OF SOURCES OF LEGAL REGULATION OF BUSINESS FINANCING - Adik Lee (Modern American Journals, 2026)
The article examines the theoretical foundations of the sources of legal regulation of business financing. Their essential characteristics are revealed and the definition of such sources is given. A comparative analysis of the sources of financial law in the field of business regulation in Russia, the USA, Germany and Uzbekistan has been carried out.
Keywords: sources of law, financing, business activities